Association Between Migraine Complicated With Restless Legs Syndrome and Vitamin D - Sun, Shuning; Liu, Chunling; Jia, Yanlu; Wu, Jun; Li, Hui; Li, Xiaonan; Zhao, Yimin (Frontiers in Neurology, 2021)
Background: This study aimed to evaluate the prevalence of restless legs syndrome (RLS) in patients with migraine and explore its association with vitamin D deficiency, aiming to provide biological support for the comorbidity of migraine with RLS, and shed new lights into clinical diagnosis and treatment. Methods: A case-control study was performed on 175 migraine patients and 151 non-headache controls. The information of all subjects concerning headache severity (VAS score), RLS, RLS severity (IRLS score), sleep quality (PSQI), anxiety and depression symptoms (HADS), and demographic data were collected. At the same time, serum 25-(OH) D levels were also measured (concentration < 20 ng/mL was defined deficiency). Afterwards, the logistic regression model was adopted to explore the risk factors for RLS in patients with migraine. Results: Compared with control group, migraine group had lower vitamin D levels [(21.10 ± 6.58) vs. (16.42 ± 5.60) ng/mL, P < 0.001], a higher rate of vitamin D deficiency (45.03 vs. 72.00%, P < 0.001), higher prevalence of RLS (6.62 vs. 22.29%, P < 0.001). Compared with pure RLS group, RLS with migraine group had lower vitamin D levels and higher IRLS score (P < 0.05). Compared with pure migraine group, migraine with RLS group had lower vitamin D levels [(17.36 ± 5.56) vs. (13.15 ± 4.42) ng/mL, P < 0.001], higher incidence of vitamin D deficiency (66.18 vs. 92.31%, P = 0.001), higher frequency of headache attacks (P = 0.004). Thereafter, the multivariate logistic regression model was employed to adjust confounding factors such as age, gender, season, frequency of headache attacks, PSQI score, and HADS score. According to the results vitamin D deficiency in patients with migraine was an independent risk factor for RLS (OR = 5.03, 95%CI: 1.2021.16, P = 0.027). Conclusions: The prevalence of RLS in migraine patients is significantly higher than that in the non-headache population. Besides, vitamin D levels decrease, while the incidence of vitamin D deficiency increases in the migraine patients complicated with RLS, and the occurrence of RLS in migraine patients is significantly related to vitamin D deficiency.